Vulnerability of The Garut District Region in Tarogong Kalam, Tarogong Kidul, Garut Kota, And Karang Pawitan Sub-District Based on Microtremor Measurement - Rahmat Setyo Yuliatmoko; Telly Kurniawan; Thomas Hardy; Yusuf Hadi Permana (Jurnal Lingkungan dan Bencana Geologi, 2020)
The Tasikmalaya M 7.3 earthquake on September 2, 2009 had an impact on Garut, damaged infrastructure and claimed many lives. From the search results there were five areas that were severely damaged by tectonic earthquake shocks, which included Pemeungpeuk, Cisompet, Cikelet, Peundeuy and Banjarwangi Subdistricts, so that earthquake mitigation measures were needed. One of the mitigations that can research how the impact is if the potential for earthquake disasters occur below the southern surface of Java. The final objective of this research is to map disaster-prone zones in Tarogong Kaler, Tarogong Kidul, Garut City, and Karang Pawitan, Garut Subdistrict, based on dominant frequency values, Vs30, seismic vulnerability indexes, and GSS (Ground Shear Strains) so that they can know the land movement that is. Retrieval of data in this study by measuring geophysicaly methods in the field. Processing data using HVSR (Horizontal to Vertical Spectra Ratio) method, then mapped with ArcGis to interpret the zoning of the study area. Based on the research, we known that the dominant frequency distribution value is between 1-5.2 Hz. The seismic vulnerability index values calculated the study area are between 3 – 45, GSS values in the study area between 3 ×10-4 - 42×10-4. By looking at the spatial distribution of the values of f0, Kg and GSS the areas of Karangmulya, Jatiasih, Sidanggalih and Godog villages are types of young volcanic sediments classified as soft soils that are easily to wave amplification and earthquake vibrations, so that they are easily damaged during large earthquakes. in this region qualify as earthquake resistant buildings to minimize damage and losses, while Sukabakti, Kersamenak, Sukajaya, and Mekargalih villages in the west with the geological conditions of the surrounding area which is hard land so that it will be safer when an earthquake occurs.